Bertahannya Pasar Tradisional Sanglah di Tengah-Tengah Pengaruh Pasar Modern di Denpasar Tahun 2000-2018 - Ismail, Raudatul; Wirasmini Sidemen, Ida Ayu; Setiowati Sunaryo, Fransiska Dewi (Humanis; Vol 24 No 4 (2020), 2020)
This study is entitled The Survival of Sanglah Traditional Market in the Middle of the Effect of Modern Markets in Denpasar in 2000-2018. Sanglah Market is surrounded by many modern markets. Economic developments that occur at this time lead to competition between the Sanglah market and the modern market in Denpasar. The research method used is the historical research method which consists of four stages, namely heuristics, source criticism, interpretation and historiography. The results of this study indicate that the Sanglah market is one of the engines of economic growth for the City of Denpasar. The rise of the development of modern markets in the city of Denpasar requires traders in the Sanglah market to innovate more in maintaining their existence. The many modern markets in Denpasar City have their own impact on traders in the Sanglah market both economically and socially, such as the decline in the income of traders, besides that the modern market also impacts on people's lifestyles.